Customers, control, and the performance of Islamic banks - Alaudin, Ahmadasri (Asian Journal of Accounting Perspectives, 2021)
Research aim: This study explores the relationship between customer fairness and trust building and the performance of bank branches. Design/Methodology/Approach: Methodologically, this relationship is first explored with no mediating variable using bivariate correlation analysis as a precursor to a more sophisticated path analysis where this relationship is hypothesized to be mediated by control systems. The data for these analyses are subjective assessments elicited from a survey of branch managers working in two different Islamic banks in Malaysia. Research Findings: Overall, the results suggest that customer trust building is an important determinant of performance relative to expectations, both directly and indirectly through the use of control systems. However, there is less support for a significant association between customer fairness building and performance. Theoretical contribution/Originality: Given the impressive growth in the size and popularity of Islamic banking around the world, it is an increasingly pertinent domain for academic research. This study has sought to contribute to this literature from the perspective of organizational dynamics and organizational performance as perceived by branch managers. It also contributes to Simons’ levers of control framework by operationalizing its belief system lever using values (i.e., trust and fairness building). Practitioner/Policy implication: Bank management both at corporate and business (operating) levels may benefit from the findings in implementing strategy and developing value-based competitive advantage in a form of trust and fairness. Limitation/Implication: The lack of support for customer building results may provide opportunity for further research into this. It would have been interesting to elicit views from a wider range of bank personnel (i.e., regular employees as well as branch managers). Whilst on the other hand it may have been beneficial to utilize more objective measurements, particularly with respect to performance. Keywords: Control systems, Fairness, Islamic banks, Malaysia, Path analysis, Trust Type of article: Research paper JEL Classification: G21, M41, M31